Lexical-Semantic Means of Lowering Language and Style in the Printed Media (Linguostylistic Studies, 2017)
The article sheds light on the role and perspective of colloquial language development and its importance for the dynamic development of the literary standards, reveals the ways to replenish the slang and jargon vocabulary of the spoken language and the reasons for their entry into the printed media. The author argues that penetration of the lexemes with lowered connotative meaning into the language of publicistics is due to their expressiveness, high evaluative potential and vividness. The vernacular vocabulary with its bright stylistic coloration facilitates its usage in mass media. The study has revealed frequent use of the obscene lexicon, which has predominantly negative connotative meaning and is usually aimed at disclosing scandalous relationships, annoying an opponent, showing someone’s insignificance or is used as a means of protecting oneself. These lexical units make the journalist’s message more expressive, creative and bright. The key findings of this study contribute to understanding of modern tendencies in the language and the impact of publicistics on the lingual reality.
Keywords: literary language; colloquial language; jargon vocabulary; obscenity; aposiopesis